ANALYSIS OF ACTORS AND ACTIVITIES IN VALUE CHAIN BUSINESS SHEEP FAULTING - Marisa, Julia; Sitepu, Sukma Aditya; Rianto, Aditya Amanda (Proceeding International Conference of Science Technology and Social Humanities; Vol 1 (2022): International Conference of Science Technology and Social Humanities, 2022)
Optimal overall processing of various company activities in a value chain, will create an advantage over stand-alone activities. This condition will eventually encourage to create a maximum profit margin. For the government, the results of this study are expected to be useful for the local government to be used as a reference in an effort to increase the competitiveness of sheep breeders. The purpose of this study was to analyze the actors involved and activities in the value chain of the sheep fattening business in the study area. This data collection technique is considered appropriate to investigate the value chain of the sheep fattening industry. The data analysis used in this study is in the form of qualitative and quantitative data analysis, with data analysis methods with value chain mapping. The results showed that the actors involved were sheep breeders, sheep processors, traders and consumers. The activities carried out by the actors/actors involved in the sheep commodity value chain have a mutually coordinating relationship and require one another. Therefore, value chain activities in the value chain commodity business do not only involve the main activity, but there are supporting activities that are involved either directly or indirectly. The actors involved include providers of production inputs, cultivators, fish processors, collector traders, consumer retailers and agencies/institutions related to the sheep commodity business in North Sumatra.